New comprehensive procedure for custom‐made total ankle replacements: Medical imaging, joint modeling, prosthesis design, and 3D printing - Belvedere, Claudio; Siegler, Sorin; Fortunato, Alessandro; Caravaggi, Paolo; Liverani, Erica; Durante, Stefano; Ensini, Andrea; Konow, Tobias; Leardini, Alberto (Journal of orthopaedic research, 2019)
ABSTRACT Many failures in total joint replacement are associated to prosthesis‐to‐bone mismatch. With recent additive‐manufacturing, that is, 3D‐printing, custom‐made prosthesis can be created by laser‐melting metal powders layer‐by‐layer. Ankle replacement is particularly suitable for this progress because of the limited number of sizes and the poor bone stock. In this study a novel procedure is presented for subject‐specific ankle replacements, including medical‐imaging, joint modelling, prosthesis design, and 3D‐printing. Three shank‐foot specimens were CT‐scanned, and corresponding 3D bone models of the tibia, fibula, talus, and calcaneus were obtained. From these models, specimen‐specific implant sets were designed according to three different concepts, and 3D‐printed from cobalt‐chromium‐molybdenum powder. Accuracy of the overall procedure was assessed via distance map comparisons between original anatomical and final metal implants. Restoration of natural ankle joint mechanics was check after implantation of each of the three sets. In a special rig, a manually‐driven dorsi/plantar‐flexion was applied throughout the passive arc. Additionally, at three different joint positions, joint torques were imposed in the frontal and axial anatomical planes. Mean manufacturing errors were found to be smaller than 0.08 mm. Consistent motion patterns were observed over repetitions, with the mean standard deviation smaller than 1.0 degree. In each ankle specimen, mobility, and stability at the replaced joints compared well with the original natural condition. For the first time, custom‐made implants for total ankle replacements were designed, manufactured with additive technology and tested. This procedure is a first fundamental step toward the development of completely personalized prostheses. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res